Involuntary treatment of schizophrenia patients 2004–2010 in Denmark. (10th May 2013) - Andersen, T. H.; Kappers, D.; Sneider, B.; Uggerby, P.; Nielsen, J.
<x xml:space="preserve">Abstract</x> Objective Treatment of schizophrenia is frequently complicated by patients' ambivalence and lack of insight into the disease, occasionally warranting involuntary treatment. This study aims to describe involuntary treatment in Danish schizophrenia patients. Method Patients diagnosed with a lifetime ICD‐10 F20 schizophrenia diagnosis and alive in the period 2004–2010 were identified in the Danish Psychiatric Central Research Register, and data were linked to The Registry of Coercive Measures in Psychiatric Treatment. Results Within the study period, a total of 18 599 admitted patients were identified, 3078 of which underwent involuntary treatment. The incidence rate for any involuntary treatment was 2.1 per in‐patient year and 1.7 and 0.3 per in‐patient year for rapid tranquilization and involuntary treatments, respectively. Somatic diseases comprised 34.5% of all involuntary treatments. Psychotropics comprised 56.9% with antipsychotics as the most common drug class (99.5%). Olanzapine was the most commonly used antipsychotic drug (33.2%). Treatment with depot injection and clozapine comprised only 13% and 4.8% of the antipsychotics used, respectively. Electroconvulsive therapy comprised 4.8% of all involuntary treatment. Conclusion Involuntary treatment involved a wide range of somatic treatment. Antipsychotic medicine was the most common psychotropic used. Involuntary treatment with depot antipsychotics and clozapine were rare.